IMPLEMENTASI LITERASI FINANSIAL PADA PESERTA DIDIK KELAS 5 DI SEKOLAH ALAM AL GIVA KOTA BOGOR - Nurhalimah; Muhammad Fahri; Munggarani Basri, Rara Genta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Technological advances have made it easier to access financial services, but ironically, this has also contributed to the increasing cases of online loan defaults and the involvement of the younger generation in online gambling due to a lack of financial literacy. This study aims to describe the implementation of financial literacy in grade 5 students at Al Giva Nature School and its impact on their financial understanding and attitudes. We collected data through observation, in-depth interviews, and documentation using a qualitative approach and case study method. The results of the study show that financial literacy is implemented through fundraising activities, saving, internal internships in the school canteen, and Friday alms, which are integrated with the school's business pillars. These activities provide students with practical experience in obtaining, saving, spending, and donating money. The impact is seen in the increasing understanding of students about sources of money, the ability to distinguish between needs and wants, the growth of saving habits, and enthusiasm for sharing. This study concludes that the implementation of financial literacy based on real activities makes a positive contribution to instilling wise financial understanding and behavior in students from an early age.